Response of Soybean Grown on a Claypan Soil in Southeastern Kansas to the Residual of Different Plant Nutrient Sources and Tillage - D. W. Sweeney; Philip Barnes; Gary Pierzynski (Kansas Agricultural Experiment Station Research Reports, 2016)
The residual from previous high rate turkey litter applications, which were based on N requirements of the previous grain sorghum crop, increased soybean yield above that obtained from the residual of P-based turkey litter applications (low rate), commercial fertilizer, or the control. Even though early soybean growth was not significantly affected by residual treatments, the greatest dry matter production at the R6 growth stage was where the N-based litter had been applied and incorporated.
Keywords: soybean